Iron- and zinc-fortified parboiled rice - Chanakan Prom-u-thai (2018)
© Springer Science+Business Media New York 2013. All rights reserved. Fortification of iron and zinc in parboiling process effectively increased iron and zinc concentrations compared with those in non-fortified parboiled rice, especially in the polished rice where most of iron and zinc is usually removed during milling process. Parboiled rice is already produced on industrial scale and traded globally as well as within each country. It is commonly consumed in South Asia and Africa where iron and zinc deficiencies in human population are widespread. Iron and zinc-fortified parboiled rice can easily and rapidly reach rice consumers in these countries without the need to alter consumption habits of local populations and establishing new market network and access. It offers highly cost-effective tool to reduce the incidences of iron deficiency in developing countries within an immediate future if it is adopted by the current parboiled rice industry.